겨울철 충남 서산 지역 PM2.5의 화학적 및 광흡수 특성 - 손세창(Se-Chang Son); 주서령(Seoryeong Ju); 이광열(Kwangyul Lee); 박승식(Seungshik Park) (한국대기환경학회지(국문), 2021)
Chemical and light absorption characteristics of PM2.5 during winter (Jan. 11~Feb. 21, 2020) at a Seosan site in Chungcheongnam-do were examined. During PM2.5 pollution episode (24-hr PM2.5>35 μg/m3), organic carbon (OC) and NO3 - were important contributors of PM2.5, accounting for 33 (on a organic mass basis) and 26% of PM2.5, respectively. Correlations of OC with elemental carbon, K+, Cl-, and SO4 2- suggest that the OC measured during the pollution episode was largely affected by biomass burning (BB) emissions. On the contrary, the OC during non-pollution episode was mainly associated with traffic emissions. Based on NO3 -/SO4 2- mass ratio, it was found that mobile sources (e.g., traffic emissions) contributed significantly to the formation of NO3 - during the pollution episode. A conditional weighted trajectory analysis indicated that PM2.5 and NO3 - during study period were dominated by local pollution rather than regional transport, but SO4 2- was dominated by regional transport. Fe solubility, expressed as fraction of soluble Fe to total Fe, was on average 5.1% (2.1~10) and influenced by primary emissions (e.g., BB) and chemical processing of secondary acidic aerosols (SO4 2- and NO3 -), but with a greater influence from chemical processing of secondary acidic aerosol particles on enhancing the solubility of Fe. Contribution of light absorption by organic aerosols to total aerosol light absorption at 370 nm varied significantly with aerosol composition (e.g., black carbon and brown carbon). Moreover, absorption Ångström exponent values of organic aerosols estimated in the wavelength range of 370~660 nm were in the range of 2.9~4.8 with an average of 4.2, which is due to light absorption by both water-soluble and insoluble organic aerosol particles. KCI Citation Count: 0